Third dose of an mRNA COVID-19 vaccine for patients with multiple myeloma. (January 2023) - Goldwater, Marissa-Skye; Stampfer, Samuel D.; Sean Regidor, Bernard; Bujarski, Sean; Jew, Scott; Chen, Haiming; Xu, Ning; Kim, Clara; Kim, Susanna; Berenson, James R.
Highlights: Patients without response to two COVID-19 vaccines can respond to a 3rd dose. Factors predict the likelihood of responses to this 3rd dose of the vaccine. Monitoring anti-spike IgG antibody levels can optimize vaccine use for MM patients. Abstract: We have reported that IgG antibody responses following two mRNA COVID-19 vaccinations are impaired among patients with multiple myeloma (MM). In the current study, sixty-seven patients with MM were tested for anti-spike IgG antibodies 0–60 days prior to their first vaccination, 14–28 days following the second dose, and both before and 14–28 days after their third dose of the mRNA-1273 or BNT162b2 vaccines. After the first two doses, most patients' (93 %) antibody levels declined to ineffective levels (<250 BAU/mL) prior to their third dose (D3). D3 elicited responses in 84 % of patients (61 % full response and 22 % partial response). The third vaccination increased antibody levels (average = 370.4 BAU/mL; range, 1.0–8977.3 BAU/mL) relative to just prior to D3 (average = 25.0 BAU/mL; range, 1.0–683.8 BAU/mL) and achieved higher levels than peak levels after the first two doses (average = 144.8 BAU/mL; range, 1.0–4, 284.1 BAU/mL). D3 response positively correlated with mRNA-1273, a > 10-fold change from baseline for the two-dose series, switching from BNT162b2 to mRNA-1273 for D3, and treatment with elotuzumab and an immunomodulatory agent. Lower antibody levels prior to D3, poorer overall response to first two doses, and ruxolitinib or anti-CD38 monoclonal antibody treatment negatively correlated with D3 response. Our results show encouraging activity of the third vaccine, even among patients who failed to respond to the first two vaccinations. The finding of specific factors that predict COVID-19 antibody levels will help advise patients and healthcare professionals on the likelihood of responses to further vaccinations.